2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6630841
|View full text |Cite
|
Sign up to set email alerts
|

Inverse kinematics for shape rendering interfaces

Abstract: Dynamically rendering the shape of an object offers a lot of new opportunities in the fields of virtual reality, design, and prototyping as bare hand interaction represents a very intutive way to explore objects. We propose a 3D-shape interface formed by a parallel kinematics connecting multiple nodes and present an inverse kinematics based on a retargeting algorithm to control these nodes. The shape is formed by simultaneously taking into account loop constraints, joint limits and user interaction points. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The connections between the nodes, which are used to render the shape, feature several joints. In [12], we showed that 3 DoFs per node are needed to render a shape. This means that M = 3 n must hold, with n the number of free nodes and M the number of overall DoFs of the device.…”
Section: B Determinacymentioning
confidence: 99%
See 3 more Smart Citations
“…The connections between the nodes, which are used to render the shape, feature several joints. In [12], we showed that 3 DoFs per node are needed to render a shape. This means that M = 3 n must hold, with n the number of free nodes and M the number of overall DoFs of the device.…”
Section: B Determinacymentioning
confidence: 99%
“…We observed that especially spherical shapes were not rendered satisfactorily by this early version of the FO as the nodes were not able to position and orient themselves properly at the same time. As shown in [12], 3 DoFs per node are needed to render a shape. To be more precise, one translational DoF (distance to the virtual surface) and two rotational DoFs (alignment normal to virtual surface) per node are required.…”
Section: Kinematic Design Of Basic Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a high damping λ S will avoid the fulfillment of the shape task and consequently lead to potentially large shape errors e S . In [14], we proposed the damping factor of the shape task to be dependent on the error resulting from the violation of constraints. We extend this approach by a dependence of λ S on the two factors B 1 and B 2…”
Section: Joint Limits and Singularitiesmentioning
confidence: 99%